Independent evolution of stratospheric temperatures in Jupiter's northern and southern auroral regions from 2014 to 2016. Issue 11 (12th June 2017) - Sinclair, J. A.; Orton, G. S.; Greathouse, T. K.; Fletcher, L. N.; Tao, C.; Gladstone, G. R.; Adriani, A.; Dunn, W.; Moses, J. I.; Hue, V.; Irwin, P. G. J.; Melin, H.; et al.
Abstract: We present retrievals of the vertical temperature profile of Jupiter's high latitudes from Infrared Telescope Facility‐Texas Echelon Cross Echelle Spectrograph measurements acquired on 10–11 December 2014 and 30 April to 1 May 2016. Over this time range, 1 mbar temperature in Jupiter's northern and southern auroral regions exhibited independent evolution. The northern auroral hot spot exhibited negligible net change in temperature at 1 mbar and its longitudinal position remained fixed at 180°W (System III), whereas the southern auroral hot spot exhibited a net increase in temperature of 11.1 ± 5.2 K at 0.98 mbar and its longitudinal orientation moved west by approximately 30°. This southern auroral stratospheric temperature increase might be related to (1) near‐contemporaneous brightening of the southern auroral ultraviolet/near‐infrared H 3 + emission measured by the Juno spacecraft and (2) an increase in the solar dynamical pressure in the preceding 3 days. We therefore suggest that 1 mbar temperature in the southern auroral region might be modified by higher‐energy charged particle precipitation. Key Points: Stratospheric temperatures in Jupiter's northern and southern auroral regions evolve independently The 1 mbar temperature in Jupiter's northern auroral region exhibited a net negligible change from 2014 to 2016 The 1 mbar temperature in Jupiter's southern auroral region exhibited a net increase of over 10 K from 2014 to 2016